(untitled) (Journal of EAHIL, 2025)
Dear all, welcome back to my column! For this issue’s “Publications and new products” column I’ve searched the web and selected news and articles on the most discussed trends related to biomedical librarianship. Once again, it’s Artificial Intelligence, Diamond Open Access and Open Science. Among the reading suggestions is a paper by Galli, Moretti, and Calciolari which discusses the case for biomedical literature reviews, arguing that AI summaries may soon reach a point where they are equivalent to current reviews of the literature, possibly making them irrelevant. The paper poses a question that I would like to pose to you too: whether "the availability of automated summaries of the literature may raise the bar of what is still worth publishing".